To find the correct process of solving \(-3^0 + 4.5\), we need to evaluate the expression step by step.
-
First, we need to recall that any number (except zero) raised to the power of \(0\) is \(1\). So, \(3^0 = 1\).
-
However, \(-3^0\) should be interpreted as \(-(3^0)\), which means \(-1\).
Now, we can evaluate the expression: \[ -3^0 + 4.5 = -1 + 4.5 = 3.5 \]
Now let's evaluate each option:
A. \(-3^0 + 4.5 = -3\cdot0 + 4.5 = 0 + 4.5 = 4.5\)
Incorrect because it misinterprets the exponent.
B. \(-3^0 + 4.5 = -1 \cdot 3^0 + 4.5 = -1 \cdot 1 + 4.5 = -1 + 4.5 = 3.5\)
Correct because it correctly evaluates \(-3^0\) as \(-1\).
C. \(-3^0 + 4.5 = -3 + 4.5 = 1.5\)
Incorrect as it misrepresents \(-3^0\).
D. \(-3^0 + 4.5 = (-3)^0 + 4.5 = 1 + 4.5 = 5.5\)
Incorrect because it wrongly treats \(-3^0\) as \((-3)^0\).
Thus, the correct answer is B.